2000
DOI: 10.1603/0022-2585-37.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Sympatry in theCulicoides variipennisComplex (Diptera: Ceratopogonidae): a Taxonomic Reassessment

Abstract: We report sympatry among larval populations of the Culicoides variipennis complex in widespread and diverse aquatic habitats throughout the United States. Six sites in California, Nevada, New Mexico, and Texas were co-inhabited by C. v. occidentalis and C. v. sonorensis, whereas 8 sites in Florida, Georgia, Louisiana, Maryland, and Texas were co-occupied by C. v. sonorensis and C. v. variipennis. No intermediate forms were identified either electrophoretically or morphologically in adults reared from field-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 21 publications
1
88
1
Order By: Relevance
“…Both viruses are transmitted by hematophagous midges of the genus Culicoides, and for BTV, its geographic range is determined by the distribution of competent Culicoides species and environmental conditions affecting vectorial capacity and virogenesis in these vectors (Mullens et al 2004;Schmidtmann et al 2011). In North America, competent vectors for BTV include Culicoides sonorensis (Holbrook et al 2000) and Culicoides insignis (Tanya et al 1992), but a potential for additional Culicoides vectors, especially for EHDV, may exist .…”
Section: Introductionmentioning
confidence: 99%
“…Both viruses are transmitted by hematophagous midges of the genus Culicoides, and for BTV, its geographic range is determined by the distribution of competent Culicoides species and environmental conditions affecting vectorial capacity and virogenesis in these vectors (Mullens et al 2004;Schmidtmann et al 2011). In North America, competent vectors for BTV include Culicoides sonorensis (Holbrook et al 2000) and Culicoides insignis (Tanya et al 1992), but a potential for additional Culicoides vectors, especially for EHDV, may exist .…”
Section: Introductionmentioning
confidence: 99%
“…The vectors of BTV are species of hematophagous midges in the genus Culicoides, and BTV infection occurs throughout tropical and temperate regions of the world (22). Culicoides sonorensis (formerly Culicoides variipennis) is the principal vector of BTV in North America (28,54). Female Culicoides insects become persistently infected with BTV and can transmit the virus to susceptible ruminants after an extrinsic incubation period (EIP) of 10 to 14 days (20,36,41).…”
mentioning
confidence: 99%
“…The presence of Culicoides midges has been reported in Mexico since 1948 (Macfie, 1948). Apparently, these types of biting midges are widely dispersed in USA and Latin America (Mullens and Dada, 1992;Holbrook et al, 2000;Lager, 2004). It has been reported that C. varipennis var.…”
Section: Discussionmentioning
confidence: 99%